STRUCTURAL GEOLOGY: THE MECHANICS OF DEFORMING METAMORPHIC ROCKS VOLUME 1 PRINCILPES - HOBBS, BRUCE; ORD, ALISON (New Delhi Elsevier, 2015)
It is a groundbreaking reference that introduces you to the concepts of nonlinear solid mechanics and non-equilibrium thermodynamics in metamorphic geology.
Keywords: Geology; Structural Geology; Rocks; Metamorphic Rocks